2016
DOI: 10.1104/pp.16.00404
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling High Light Responses from Singlet Oxygen Retrograde Signaling and Spatial-Temporal Systemic Acquired Acclimation

Abstract: Distinct ROS signaling pathways initiated by singlet oxygen ( 1 O 2 ) or superoxide and hydrogen peroxide have been attributed to either cell death or acclimation, respectively. Recent studies have revealed that more complex antagonistic and synergistic relationships exist within and between these pathways. As specific chloroplastic ROS signals are difficult to study, rapid systemic signaling experiments using localized high light (HL) stress or ROS treatments were used in this study to uncouple signals requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 81 publications
1
46
0
Order By: Relevance
“…A simplistic model of retained alterations in leaf structure is difficult to reconcile with a leaf developed largely in the absence of stress, with newly developed chloroplasts displaying an altered requirement for NPQ. Contributions of systemic signals emanating from the exposed tissue to the newly developed or emerging tissue, such as carotenoid oxidation products, reactive oxygen species, or mobile small RNAs (Carmody et al, 2016;Lewsey et al, 2016;Ramel et al, 2012), or the direct exposure of the apical meristem to EL in this study might underpin our observations. To confirm whether this is an SAA-mediated phenomenon may involve confirming the transmission of these traits in SAA-impaired mutants such as RbohD (Miller et al, 2009 comparable with pre-existing leaves, but this was not observed.…”
Section: Transmission Of Select Psii Traits Indicative Of Mitotic Imentioning
confidence: 71%
See 3 more Smart Citations
“…A simplistic model of retained alterations in leaf structure is difficult to reconcile with a leaf developed largely in the absence of stress, with newly developed chloroplasts displaying an altered requirement for NPQ. Contributions of systemic signals emanating from the exposed tissue to the newly developed or emerging tissue, such as carotenoid oxidation products, reactive oxygen species, or mobile small RNAs (Carmody et al, 2016;Lewsey et al, 2016;Ramel et al, 2012), or the direct exposure of the apical meristem to EL in this study might underpin our observations. To confirm whether this is an SAA-mediated phenomenon may involve confirming the transmission of these traits in SAA-impaired mutants such as RbohD (Miller et al, 2009 comparable with pre-existing leaves, but this was not observed.…”
Section: Transmission Of Select Psii Traits Indicative Of Mitotic Imentioning
confidence: 71%
“…Indeed, the spread of systemic acquired resistance to biotic stresses has been reported to be accompanied by histone modifications including methylation, acetylation, and replacement (Jaskiewicz, Conrath, & Peterhänsel, 2011;March-Díaz et al, 2008). A common output of SAA mediated EL stress priming is the pre-emptive accumulation of photoprotection associated transcripts (Carmody et al, 2016;Gordon et al, 2013;Rossel et al, 2007). Although propagation of this is often attributed to mobile signals generated at the site of EL stress (Carmody et al, 2016;Ramel et al, 2012;Suzuki et al, 2013), a hitherto untested hypothesis is the contribution of maintained chromatin variation towards sustained photoacclimation in newly developed tissue (memory).…”
Section: The Methylome Is Unperturbed By Single and Recurring El Stmentioning
confidence: 99%
See 2 more Smart Citations
“…In a very recent study, however, the role of EX1 and EX2 in an acclimation response to high light-induced transcriptional reprogramming has also been demonstrated (Carmody et al, 2016). To get insight into these distinctive cascades, we compared the β-CC-induced SORGs and EX1-FtsH2-dependent ESORGs, with the aim to explain the common and distinct molecular characteristics and enlighten their coexistence.…”
Section: Resultsmentioning
confidence: 99%